2011
DOI: 10.4018/jmbl.2011100104
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Challenges of Supporting Collaborative Mobile Learning

Abstract: Mobile technology opens up opportunities for collaborative learning in otherwise remote contexts outside the classroom. A successful realization of these opportunities relies, however, on mobile learning activities providing adequate collaboration structures. This article presents an empirical study aimed at examining the role played by mobile devices, teachers and task structures as a means for collaborative learning in geometry. The study focused on the analysis of the nature of collaboration that unfolded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
3
0
3
Order By: Relevance
“…Part-time instructors who had limited access to mobile devices were less experienced and less comfortable with them than those who either were assigned or owned a mobile device. This finding is important in light of research by Eliasson et al (2011) and Nouri et al (2011), who found that mobile technologies get in the way of outdoor education if insufficient time is spent considering the role of the devices and desired communication and collaboration with them. To effectively integrate mobile technologies, instructors must have sustained access and training.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Part-time instructors who had limited access to mobile devices were less experienced and less comfortable with them than those who either were assigned or owned a mobile device. This finding is important in light of research by Eliasson et al (2011) and Nouri et al (2011), who found that mobile technologies get in the way of outdoor education if insufficient time is spent considering the role of the devices and desired communication and collaboration with them. To effectively integrate mobile technologies, instructors must have sustained access and training.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, mobile devices may serve as distractions to learning if the environment is not adequately designed (Eliasson, Cerratto-Pargman, Nouri, Spikol, & Ramberg, 2011;. These authors found that mobile devices can interfere with student interactions in the physical environment because of the many apps, tools, and features on the device Nouri et al, 2011). Additionally, they found that interpersonal communication and collaboration can be compromised by mobile devices if the learning tasks are not planned effectively Nouri et al, 2011).…”
Section: K-12 Educationmentioning
confidence: 99%
“…El aprendizaje colaborativo puede ser considerado como una estrategia efectiva para promover los logros de los alumnos, el pensamiento de orden superior, habilidades de argumentación y explicación, autonomía, interdependencia, retención, resolución de problemas, auto-regulación y uso de estrategias metacognitivas (Roseth, Johnson y Johnson, 2008;Nouri, Cerratto-Pargman, Eliasson y Ramberg, 2011).…”
Section: Modos De Interacción En M-learning M-learning Colaborativounclassified
“…Colaborative Learning) introduce tecnología digital en las tareas de aprendizaje colaborativo. Esto trae aparejado los beneficios enunciados en el párrafo anterior sumados a: aumento de la motivación y mejoras de los procesos de elaboración, diálogo, debate, pensamiento divergente (Dillenbourg, Järvelä y Fischer, 2009;Nouri et al, 2011).…”
Section: El Aprendizaje Colaborativo Soportado Por Computadora (Csclunclassified
See 1 more Smart Citation